На задворках Великой империи: роман в 2-х книгах (Валентин Пикуль) - Пикуль Валентин Саввич
Экземпляры: ф. 1 (20150122) / Инвентарный номер: 101940 / Цена: 30.00 / Авт.знак: П 32 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6